Development of the exercise self-efficacy scale for Chinese older adults - Hong G. (2014)
Exercise self-efficacy is one of the most important factors that influences older person's exercise behavior. In China, it was reported that less than half of older people residing in urban areas engage in exercise regularly and lack of perception was alleged to be a major reason. This study was designed to develop and examine the psychometric properties of the Exercise Self-efficacy Scale for Chinese Older Adults (ESES). An instrument development design was used and convenient sampling was employed to recruit 402 Chinese older adults to participate in this study. Five steps of the instrument development process included identifying the exercise self-efficacy concept, generating the items, determining the format, reviewing the items by expert and testing of validity and reliability. The ESES is a 30-item, 4-point Likert Scale. It comprises of six dimensions, namely, lack of motivation, lack of support, health condition, time barriers, lack of facilities and environmental barriers. The new scale demonstrates an acceptable content validity index and construct validity. Its criterion-related validity in line with the Physical Activity Questionnaire developed by Voorrips and colleagues was also reported. The ESES developed in this study can be used as research and clinical tools to measure exercise self-efficacy of Chinese older adults.